Intramedullary cortical fragment in tibial nailing: push it, remove it or ignore it? - Branca Vergano, Luigi; Prezioso, Vito; Monesi, Mauro (Acta Biomedica Atenei Parmensis, 2021)
Intramedullary nailing of long bones is a safe procedure, with excellent long-term results. Even in apparently simple fractures, many complications may arise. Incarceration of a cortical fragment in the medullary canal is a fearsome situation, which may lead to severe complications and, consequently, poor outcomes. The surgeon should be aware of this risk and, after careful analysis of the pre-operative imaging, must remove or, at least, disengage the fragment from the medullary canal.